Myocardial Bridging, A Neglected Anomaly in Acute Coronary Syndrom: Case Report - Gita Pangestu Hapsari; Gabriel Riadhy Tanok Harmany; Daniel Dionisius Sianipar; Adityo Nugroho Kalandoro; A. Sari Sri Mumpuni (Universitas Brawijaya, 2022)
ABSTRACT Background: Myocardial Bridging (MB) is an anomaly characterized by an intra-myocardial route of a segment of one of the major coronary arteries. Functional myocardial bridging is less commonly observed on angiography (0.5–16%) and can range from 4 to 80 mm in length. This case report elaborates about a case of a symptomatic MB occurrence in a patient manifesting as an acute coronary syndrome.Case presentation: A 66 years old female presented to ER with a typical angina gradually increasing since 1 week ago. Associated symptoms were episodic syncope, dyspnea, and dyspepsia. physical examination reveals, vital signs are within normal limits. The cardio-pulmonary examination was unremarkable. Electrocardiogram (ECG) showed inverted T waves on V1-V4, cardiac biomarker enzymes were not increased, chest X-ray revealed an enlarged heart, echocardiography showed a left ventricular hypertrophy (LVH) with normal left ventricle ejection fraction (LVEF). Nitrate, aspirin, and P2Y12 inhibitor were then administered in the ER, and the patient was then transferred to catheterization lab. CT-Angiography showed a MB in the middle left anterior descending (LAD), the patient was then treated with bisoprolol as a maintenance therapy.Conclusion: MB, if presenting symptomatically, especially as an acute coronary syndrome (ACS), may become lifeŧhreatening if not recognized and treated appropriately. Flow normalization and symptom management in such circumstances are best achieved through revascularisation via percutaneous coronary intervention (PCI) and drug therapy by using beta-blocker.Keywords: Acute coronary syndrome, case report, epicardial artery, myocardial bridging